Relationship Between Physical Workload, Work Fatigue, and Drinking Water Consumption to Work Productivity of Brickmakers - Falya Ariestaniaji Devi; Yuliani Setyaningsih; Baju Widjasena (Universitas Ahmad Dahlan, 2023)
Background: Work productivity is the ability of the workforce to produce several goods per unit of time. Several factors, such as physical workload, work fatigue, and drinking water consumption, can cause high or low levels of work productivity. Method: This research was conducted in a brick-making business in Kaligayam Village, Tegal Regency, in August 2022 using an analytic observational research method and a cross-sectional approach. The sample in the study consisted of 42 workers and was analyzed using the Chi-Square Test with a confidence level of 95%. The instruments in this study were questionnaires to determine drinking water consumption and work productivity, as well as a physical workload measurement tool, namely the oximeter, and a work fatigue measurement tool, namely the reaction timer. Results: The physical workload (OR= 0.133; CI= 0.032-0.563; p<0.05), work fatigue (OR = 0.195; CI = 0.042-0.914; p<0.05), drinking water consumption (OR = 11.250; CI = 2.100-60.267; p<0.05) had a relationship to work productivity. Conclusion: There is a relationship between the variables of physical workload, work fatigue, and drinking water consumption on the work productivity of brickmakers. Elderly workers should do work with a light workload, workers can rest for 30 minutes every 4 hours of work, make the most of their rest time, and there is a need for workers' self-awareness to consume fluids according to NIOSH rules with a total of ≥6 liters per day.